Monitoring training load and fatigue in professional rugby league - Nielsen, M. J. (Journal of Australian Strength and Conditioning, 2020)
Monitoring training load and fatigue is crucial to ensuring athletes are in peak condition to perform during competition. Several studies have examined methods of monitoring training load and fatigue in rugby league athletes. However, a holistic monitoring approach which integrates their recommendations is yet to be described in the literature. Therefore, the purpose of this review is to propose an integrated approach of monitoring training load and fatigue in rugby league athletes based on a review of potential monitoring tools. Three literature databases (SPORTDiscus, Pub Med and Google Scholar) were searched to identify a total of 39 peer-reviewed articles which contained information relevant to the area of interest. A single measure representative of an athlete's overall health state does not exist, therefore it is recommended that practitioners utilise a mixed-methods approach to monitoring rugby league athletes. Analysing a combination of internal and external variables is recommended to quantify training load. Sessional RPE (sRPE) provides an accurate quantification of internal load, while GPS derived variables such as total distance, high speed (up to 5.0m/s) distance and total collisions are recommended for monitoring external loads. When expressed as acute and chronic loads, research supports the use of total distance and sRPE as monitoring tools to prevent injury and assess athlete preparedness in rugby league. Well-being questionnaires and tests of neuromuscular function such as the counter-movement jump and plyometric pushup are valid methods of assessing fatigue. Modification of training load or the initiation of a recovery strategy is recommended if moderate to large changes (0.9-1.3x CV) are observed in more than one measure of fatigue used within the monitoring process.